2017
DOI: 10.1088/1748-9326/aa6bfe
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment and reuse in urban agriculture: exploring the food, energy, water, and health nexus in Hyderabad, India

Abstract: Nutrients and water found in domestic treated wastewater are valuable and can be reutilized in urban agriculture as a potential strategy to provide communities with access to fresh produce. In this paper, this proposition is examined by conducting a field study in the rapidly developing city of Hyderabad, India. Urban agriculture trade-offs in water use, energy use and GHG emissions, nutrient uptake, and crop pathogen quality are evaluated, and irrigation waters of varying qualities (treated wastewater, versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 43 publications
(23 reference statements)
1
33
0
1
Order By: Relevance
“…The syntheses of three existing studies and this study indicated that the irrigated crop systems resulted in diverse environmental impacts ranging from energy consumption and global warming to water and soil quality impacts [15][16][17]. The top contributors varied across different environmental impact categories, which suggested that different strategies should be adopted for effectively remediating the corresponding environmental impacts.…”
Section: Comparison With the Existing Agricultural Lca Studies Using mentioning
confidence: 80%
See 2 more Smart Citations
“…The syntheses of three existing studies and this study indicated that the irrigated crop systems resulted in diverse environmental impacts ranging from energy consumption and global warming to water and soil quality impacts [15][16][17]. The top contributors varied across different environmental impact categories, which suggested that different strategies should be adopted for effectively remediating the corresponding environmental impacts.…”
Section: Comparison With the Existing Agricultural Lca Studies Using mentioning
confidence: 80%
“…Munoz et al [17] and this study excluded wastewater treatment processes from the system boundary, since municipal wastewater is treated to meet the discharge standard regardless of reuse as an irrigation source. In contrast, Moretti et al [15] and Miller-Robbie et al [16] included wastewater treatment processes in the system boundary. Also, the assessed crop types and geographical contexts varied significantly.…”
Section: Comparison With the Existing Agricultural Lca Studies Using mentioning
confidence: 99%
See 1 more Smart Citation
“…In agriculture, issues such as (a) irrigated agriculture [44,110], (b) wastewater treatment and reuse in urban agriculture [111], (c) food waste [112], (d) agricultural water management [71,113], and (e) the role of phosphorus (P) in nexus relations [103] were covered. In the energy sector, issues such as (a) bioenergy [86,114,115], (b) water consumption during energy production [116], and (c) impact on aquatic species through the release of thermoelectric effluents [68] were considered.…”
Section: Context Of Applicationmentioning
confidence: 99%
“…When it comes to the research scales, the prevailing opinions largely see Nexus as the local scale that often proved to be unsustainable, owing to inadequate cross-sectoral synergies. In recent times, more scholars turn to the study of Nexus system at city level [29][30][31][32]. As is well known, urbanization is prevalent worldwide, with the global urbanization rate reaching 54% in 2017.…”
Section: Introductionmentioning
confidence: 99%